Nacionalismo e igreja : a Igreja Luterana-Sínodo de Missouri nos "porões" do Estado Novo - Marlow, Sérgio Luiz (2006)
The republican period called New State not mark only the permanence of Getúlio Vargas in the command of the Brazilian nation, also marks the mediation of the proper Brazilian State in the life of that they inhabited in ground Brazilian. A good example of this is the nationalistic proposal the Brazilian Government that, from the year of 1938, through a series of rules, desired that all, especially the foreign immigrants and its descendants, to “Brazilianize". This proposal reached and reverberated all the groups of immigrants, but in special the Germans who perfectly understood to be possible to be Brazilian and to cultivate cultural traces of the native land-mother, Germany. These immigrants and its descendants had been reached especially through institutions that were on they as: the sporting and cultural associations, press and the Church. In this direction, the present study intends to observe and to tell the action of the Brazilian State with the Luteran Church: Missouri Synod, as well as the reaction and position of the related ecclesiastical institution front to the nationalistics proposals imposed by the Vargas Government. At the same time, to perceive which was the existing relation between the Luteran Church - Missouri Synod together to the Germans descendants in whom it concerns to the preservation of cultural and social traces with Germany through the practical of the Germanism.